Synthesis, characterization and sorption studies of aromatic compounds by hydrogels of chitosan blended with β-cyclodextrin- and PVA-functionalized pectin. Issue 26 (18th April 2018) - Filho, Cesar M. C.; Bueno, Pedro V. A.; Matsushita, Alan F. Y.; Rubira, Adley F.; Muniz, Edvani C.; Durães, Luísa; Murtinho, Dina M. B.; Valente, Artur J. M.
Abstract : Complex coacervation of chitosan with β-cyclodextrin- and poly(vinyl alcohol)-functionalized pectin: ability for simultaneous removal of six different aromatic compounds. Abstract : Petroleum comprises the monoaromatic and polycyclic aromatic hydrocarbons, which exhibit acute toxicity towards living animals. Consequently, their removal from natural environment is a priority challenge. On the other hand, biomaterials are increasingly being used as adsorbents. Pectin and chitosan are well-known polysaccharides able to form coacervate hydrogels. Aiming an increase of sorption ability by hydrophobic compounds, pectin was also functionalized with two amphiphilic compounds: β-cyclodextrin (β-CD) and poly(vinyl alcohol) (PVA). Both the modified pectin and the hydrogels were evaluated using nuclear magnetic resonance (NMR), infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). The hydrogels were further characterized in terms of thermogravimetric analysis (TGA) and swelling kinetics. The interaction between the hydrogel and mix solutions containing six different aromatic compounds (BTXs and the following PAHs: pyrene, benzo(b)fluoranthene and benzo(a)pyrene) has been evaluated through sorption isotherms and kinetics. The mechanism of sorption interaction and the selectivity of the adsorbents towards different aromatic compounds were discussed. The results clearly show that the presence of β-CD and PVA into gel leads to an increase in the removal efficiency of both, BTXs and PAHs. The gels were subjected to two sorption/desorption cycles to have an assessment of the capability of adsorbents for re-use. Finally, the sorption quantification of those six aromatic compounds from a real gasoline sample onto gels has been tested.